1992
DOI: 10.1192/bjp.160.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphic Evidence of Fluctuating Asymmetry in Schizophrenia

Abstract: Fluctuating asymmetry provides a measure of an organism's capacity to buffer adverse factors that could disturb its development. It is estimated from the differences between theoretically identical right- and left-sided structures. Dermatoglyphic fluctuating asymmetry has been recently used to investigate developmental disorders. Fingerprints and palm prints of schizophrenic patients, which had been the subjects of an earlier report of conventional dermatoglyphic trait frequencies, were reanalysed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 22 publications
2
73
0
Order By: Relevance
“…Dermatoglyphic variables are either qualitative (patterns formed by dermal ridges and creases) or quantitative (counts of ridges or measurements of angles) [38]. The most common traits used for right-left asymmetry are finger and palmar ridge counts, palmar atd angles [1,81], ridge patterns on the fingertips, and palmar flexion crease patterns.…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
See 3 more Smart Citations
“…Dermatoglyphic variables are either qualitative (patterns formed by dermal ridges and creases) or quantitative (counts of ridges or measurements of angles) [38]. The most common traits used for right-left asymmetry are finger and palmar ridge counts, palmar atd angles [1,81], ridge patterns on the fingertips, and palmar flexion crease patterns.…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
“…The authors found this approach to be more sensitive than traditional approaches to right-left asymmetry in a sample of schizophrenic patients. For ridge patterns (arches, radial loops, ulnar loops, and whorls), pattern discordance is used [38,86,87]. For example, if right and left index fingers both have the same ridge pattern (e.g., whorls on both fingers), then the patterns are concordant.…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, FA increases with exposure to chemical pollutants [7,8,[11][12][13][14], elevated predation risk [6,14,15], high population density [16,17], and ecosystem disturbances, including extreme temperatures in nonhuman animals [4,13,[18][19][20]. In humans, inbreeding [5], poor health conditions, and various neurological disorders, such as schizophrenia, attention deficit disorder, developmental delays in childhood, and Down syndrome are positively associated with FA [21][22][23][24][25].…”
Section: Open Accessmentioning
confidence: 99%